2021
DOI: 10.3233/jpd-202374
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1 on the Field of Parkinson’s Disease: Offense, Defense, or a Player on the Bench?

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disease worldwide. Considering the devastating symptoms, high prevalence, and lack of definitive diagnostic test, there is an urgent need to identify possible biomarkers and new therapeutic targets. Genes identified and/or proposed to be linked to PD encode proteins that fulfill diverse roles in cellular functions. There is a growing interest in identifying common traits which lead to the disease. Long non-coding RNAs have recently emerged as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 83 publications
(90 reference statements)
0
18
0
Order By: Relevance
“…Neat1_1 is high abundance and exhibits a high expression in a wide range of tissues. 19 Nonetheless, in contrast to the Neat1_2 isoform, the shorter Neat1_1 isoform has no an integral element of paraspeckles; however, it appears as microspeckles and thus may contain other effects that have not been discovered. 43 Additionally, Sasaki et al 45 indicated that the knockdown of the production of Neat1_2 can lead to paraspeckle elimination even in the presence of intact Neat1_1.…”
Section: The Course Of Neat1mentioning
confidence: 97%
See 4 more Smart Citations
“…Neat1_1 is high abundance and exhibits a high expression in a wide range of tissues. 19 Nonetheless, in contrast to the Neat1_2 isoform, the shorter Neat1_1 isoform has no an integral element of paraspeckles; however, it appears as microspeckles and thus may contain other effects that have not been discovered. 43 Additionally, Sasaki et al 45 indicated that the knockdown of the production of Neat1_2 can lead to paraspeckle elimination even in the presence of intact Neat1_1.…”
Section: The Course Of Neat1mentioning
confidence: 97%
“… 42 , 43 Paraspeckle is a complex consisting of subnuclear ribonucleoprotein within interchromatin, which plays a vital role in modulating transcription and RNA processing mainly via regulating RNA and protein editing and serving as a sponge targeting to various microRNAs. 19 There are two subtypes of mono-exonic isoforms transcribed from the Neat1 locus from chromosome 11, known as shorter Neat1_1 with 3684 nucleotides and longer Neat1_2 with 22,743 nucleotides. 19 , 44 The shorter Neat1_1 isoform (3.7 kb in human) is polyadenylated, 23 whereas the longer 23 kb subtype of Neat1_2 is not polyadenylated.…”
Section: The Course Of Neat1mentioning
confidence: 99%
See 3 more Smart Citations